Faktor Risiko Yang Mempengaruhi Kejadian Skabies Di Indonesia : Literatur Review - Riyana Husna; Tri Joko; Nurjazuli Nurjazuli (POLTEKKES KEMENKES MANADO, 2021)
Scabies is a skin disease caused by infestation and sensitization of the Sarcoptes Scabiei v. Hominis mite that occurs in communities, groups, or families living in dense, low economy, and low knowledge. Maintenance of personal hygiene strongly determines the health status, where the individual consciously and on the personal initiative to maintain health dan prevent disease. Objective: Know more about the personal effect of hygiene on the incidence of scabies. Methods: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results: There is a significant influence between personal hygiene habits, environmental sanitation, physical conditions of water, level of knowledge, density of room occupancy, age, sex, room ventilation area, bed, keteter installation, length of stay and water bacteriological examination. with the incidence of scabies. Conclusion: There is a significant relationship between personal hygiene, environmental sanitation, physical water conditions, level of knowledge, age, occupancy density. someone with an incidence of scabies